Improving Athletes' Mental Health Through Self-Talk and Progressive Muscle Relaxation on the Performance of Aquatic Athletes at The Polaris Water Park Pool n Demak Regency - Sungkowo, Sungkowo; Sobihin, Sobihin; UN, Rizam Ahada; Wicaksono, Anggit; Sungatno, Sungatno; Azizah, Ifa Nurul; Latif, Abdul; Fadillah, Imron (Universitas Negeri Semarang, 2025)
Tension and stress during competition often lead to changes in psychological functioning, such as reduced concentration, loss of focus, increased anxiety, or, from a somatic perspective, increased muscle tension. Mental health can be affected by tension, which is seen as a result of physical interactions. Self-talk is a